The oxford india Tagore: selected writings on education and nationalism (OUP, 2009)
The Oxford India Tagore focuses on Rabindranath Tagore's views on nationalism and his work on education through his essays, letters, lectures, addresses, and poetry edited by Uma Das Gupta. Tagore's writings are given as substantial excerpts or as full texts in order to enable the reader to follow his argument closely and seriously. Divided into five sections - 'Autobiographical', 'Founding a New Education', 'The Problem of India', 'East and West in the Scientific Age', and 'A Self-Respecting Nationalism as Our Salvation' - the volume takes readers closer to Tagore's life and thought, and shows how persistently he sought a solution to the problems of his times in a new and creative education and in national self-reliance, rather than in the political road to the Western model of a territorial nation-state. The book makes it clear that in many ways Tagore's educational work and his own nationalism were rooted in an original vision of India's history which amounted to a deviation from both the colonialist historiography and the nationalist ideology of those times. The book will be a valuable addition to the 'Oxford India' series which include the writings of Ghalib, Premchand, Ramanujan, Nehru, and Gandhi. This edition will appeal to all those who adore Tagore, as also students and researchers of Indian history, culture, and literature.